An initial psychometric evaluation of the APS-POQ-R in acute pain presenting to the emergency department. (December 2021) - Hughes, James A.; Jones, Lee; Potter, Joseph; Wong, Alixandra; Brown, Nathan J.; Chu, Kevin
Abstract: Aim: The purpose of this study was to examine the psychometric properties of a modified version of the American Pain Societies – Patient Outcome Questionnaire - Revised edition in adult patients presenting with acute pain to the emergency department. Background: There is a lack of validation and use of patient-reported outcome measures of pain care in the adult emergency setting. Design: Prospective psychometric evaluation. Methods: Adult patients who had presented with acute pain were invited to participate in the study after their emergency department care. The Questionnaire was administered by one of the investigators. Exploratory factor analysis (principal axis factoring) was used to explore items mapping to constructs. The number of constructs with an Eigenvalue closest to 1 was considered the correct fit for the data. Assessment of the analysis was conducted using the Kaiser-Meier-Olkin test of sampling adequacy, and the fit was assessed using Bartlett's test of sphericity. Results: The Questionnaire demonstrated construct validity in these patients. Exploratory factor analysis demonstrated five constructs. The tool demonstrated discriminatory ability based on patient urgency, and subscale measurement was associated with patient satisfaction with care Conclusions: The Questionnaire has demonstrable construct validity in adult patients presenting with acute pain to the ED.